PESAN BEDHAYA BANYU NING KALI BAGI AKUNTANSI MANAJEMEN AIR: PENDEKATAN EKOFENOMENOLOGI - Whedy Prasetyo (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2020)
The local wisdom of bedhaya banyu ning kali dance to express management accounting of water as the aim of this study, with the qualitative approach of ecophenomenology used. The results of this study make the added value of local wisdom in identifying, recognizing, quantifying, reporting, and guaranteeing information on water, rights and claims, and obligations to water in water accounting. The activity manifests thanks to the perfection of human life for the generosity of the soul over the gift of water as source life. Bedhaya banyu ning kali dances this time provide evidence that the continuity of springs is not a factor in the size and location of water, but it is necessary to include how humans preserve it, as a manifestation of life activities not only today, but forever or hereditary. Embodiments that provide additional information in the GRI 300 sustainability report on Environmental Impacts, especially GRI 303-3 for the sustainability of water use.